2017
DOI: 10.1007/s11095-017-2097-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Charges on the Cellular Uptake of Liposomes Investigated by Live Cell Imaging

Abstract: This study provides a better understanding on the cellular uptake mechanisms of the liposomes, which could contribute significantly to development of liposome-based drug delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…The presence of a positive charge on the liposomal surface incorporates a greater capacity to be internalized due to their potential interaction with the negatively charged cell membrane [59]. In a recent study by Kang et al, it was reported that cationic liposomes exhibited higher uptake due to their potential electrostatic interaction with cells [60]. The results of our cellular uptake studies were in agreement with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of a positive charge on the liposomal surface incorporates a greater capacity to be internalized due to their potential interaction with the negatively charged cell membrane [59]. In a recent study by Kang et al, it was reported that cationic liposomes exhibited higher uptake due to their potential electrostatic interaction with cells [60]. The results of our cellular uptake studies were in agreement with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Although in the present work the endocytic mechanisms were not investigated, we speculate that the difference in the extent of internalisation between the free prodrug and the pH-sensitive liposomes could rely on the involvement of distinct uptake modalities and/or kinetics of intracellular processing. There is compelling evidence showing that liposome/nanoparticle uptake is influenced by a multitude of parameters, including nanocarrier size 52,54 , surface charge 55,56 and hydrophobicity 56,57 , lipid composition 58,59 , shape 53,56 and cell type 53,54 .…”
Section: Discussionmentioning
confidence: 99%
“…The zeta potential was 16.6 ± 1.7 mV before the addition of heparin and decreased to 11.8 ± 1.4 mV after heparin electrostatic bonding. The fact that the charge remained positive, making this a cationic liposome, is an advantage, because these are preferably endocytosed by targeted cells as they are more attracted by the negatively charged cell membrane, improving the cellular concentration of the molecule of interest [20,21].…”
Section: Resultsmentioning
confidence: 99%